Calculations of binding energies of hydrocarbons for mathematical model design for the octane numbers prediction in the compounding process; Химия и химическая технология в XXI веке; Т. 2 - Petrova A. A. (Секция 7. Химия и химическая технология, 2011)
Заглавие с титульного листа